Identifying the Translation Techniques Used in the Subtitle of Luca Movie - Saputra, Aldino; Syarfi, M; Dahnilsyah, Dahnilsyah (Universitas PGRI Sumatera Barat, 2024)
This study aims to identify, analyze, and discuss the translation techniques used in the subtitle of an animated movie, as well as the phenomena found during the research process. The methodology used in this research is a qualitative analysis with a descriptive approach, but a simple quantitative approach is applied to find out the most dominant techniques. The utterances of two main characters in the film are collected, which are then categorized by type according to the theory proposed by Molina and Albir. These utterances are then analyzed and described accordingly. The research findings show that there are 13 out of 18 techniques used in the subtitle, with literal translation (146 data) as the most dominant technique. This result is in line with previous studies on the similar topic, which also have literal translation as the most dominant technique used. In summary, it can be said that there are only a few translation techniques that are actually suitable in translating movie subtitles. As the implication of this study, this research contributes to the study of language in film media and knowledge enrichment for those who are interested in translation techniques.